2020
DOI: 10.1016/j.heliyon.2020.e05294
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing internal cavity modulation of corn starch microcapsules

Abstract: Swelling of normal corn starch granules through heating in water leads to enlargement of the starch particles and a corresponding increase in internal cavity size. Through control of the swelling extent, it is possible to tune the size of the internal cavity for the starch microcapsules (SMCs). The swelling extent can be controlled through regulation of the swelling time and the swelling temperature. Since the swelling extent is correlated with particle size and solubility, these aspects may also be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…37 It has been shown that amylose is tightly bound between molecules and that starch with a high amylose content has polar groups that are not easily exposed; thus, under the same conditions, starch with a higher amylopectin content has greater solubil- ity and swelling. 38 These results were consistent with the reduction in amylopectin content after fermentation.…”
Section: Determination Of the Solubility And Swelling Power Of Starchsupporting
confidence: 85%
“…37 It has been shown that amylose is tightly bound between molecules and that starch with a high amylose content has polar groups that are not easily exposed; thus, under the same conditions, starch with a higher amylopectin content has greater solubil- ity and swelling. 38 These results were consistent with the reduction in amylopectin content after fermentation.…”
Section: Determination Of the Solubility And Swelling Power Of Starchsupporting
confidence: 85%
“…The rough and porous surface structure of MPS was eliminated by water immersion and the smooth surface showed on MPSw, which proved that the starch swelling of MPS in water immersion (Figure 2a, b, and c; Wulff et al, 2020). The crystal of starch disappeared after water immersion that consistent with the results of particle size (Figure 2b and c).…”
Section: Sem Analysis Of Mps and Mpswsupporting
confidence: 76%
“…the extension of storage time, the width of particle size distribution was increased, which was due to the water absorption and swelling of MPS (Figure1b;Wulff et al, 2020). The Swell of MPS facilitated the escape of procyanidins, and the proportion of large particles increased with the soaking time(Escobar-Puentes et al, 2020).…”
mentioning
confidence: 98%